Formation of NDMA and halogenated DBPs by chloramination of tertiary amines: The influence of bromide ion - Le Roux, J.; Gallard, H.; Croué, Jean-Philippe (American Chemical Society, 2012)
The formation of NDMA and other DBPs (including THMs, HANs, and HKs) has been investigated by chloramination of several tertiary amines in the absence and presence of bromide ion. NDMA formation from the most reactive tertiary amines (e.g., dimethylaminomethylfurfuryl alcohol or DMP30) was enhanced in the presence of bromide due to the formation of brominated oxidant species such as bromochloramine (NHBrCl) and the hypothetical UDMH-Br as an intermediate. The formation of NDMA by chloramination of less reactive model compounds was inhibited in the presence of bromide. This can be explained by competitive reactions leading to the production of brominated DBPs (i.e., THMs). In the presence of bromide, the formation of brominated THMs during chloramination can be attributed to the presence of small amounts of HOBr produced by the decomposition of chloramines and bromamines. The results are of particular interest to understand NDMA formation mechanisms, especially during chloramination of wastewaters impacted by anthropogenic tertiary amines and containing bromide ion.